Analisis Unsur Narasi: Studi Kasus Cerita Alkitab untuk Anak Sekolah Minggu - Siahaan, Sanggam; Situmeang, Siska Anggita; Siahaan, Basar Lolo (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. This research investigates various narrative elements in 10 Bible Stories for Sunday School children published on the internet. The design of this research is a qualitative method. The research showed that the narrative styles of stories with progressive plots, verbs that do not cause conflict, tension, and suspense, and conjunctions as transitional signals in a series of events can fit the comprehension level of Sunday School children in the 5–7-year-old category and the 8–9-year-old category. The narrative styles of stories which deviate from the progressive plot with verbs that cause various conflicts, tensions, and suspense, and various transition signals in a series of events are interesting for Sunday School Children in the 10–13-year-old category and the 14–16-year-old category.Abstrak. Penelitian ini meneliti berbagai unsur narasi dalam 10 cerita Alkitab untuk Anak Sekolah Minggu yang dipublikasi di internet. Desain penelitian ini adalah metode kualitatif. Hasil penelitian menunjukkan bahwa cerita model narasi dengan plot progresif, verba yang tidak menyebabkan konflik, ketegangan, dan suspens, serta konjungsi sebagai penanda transisi rangkaian peristiwa sesuai dengan tingkat pemahaman Anak Sekolah Minggu usia 5-7 tahun dan usia 8- 9 tahun. Cerita model narasi dengan plot menyimpang dari progresif, verba yang menyebabkan berbagai konflik, ketegangan, dan suspens, serta berbagai penanda transisi rangkaian peristiwa menarik bagi Anak Sekolah Minggu usia 10-13 tahun dan usia 14-16 tahun.